Propuesta de apoyo para la integración escolar de alumnos en situación de discapacidad física (Educational Perspectives Magazine (REPED), 2022)
Social attitudes toward people suffering from disabilities have evolved over time from absolute rejection to the current requirement of full integration. In the decade of the sixties, there was a broad rejection of special education schools, which gradually changing its course, from a clinical approach and welfare, to one of education.In our country a decade ago are being carried out activities aimed at social and educational integration of people experiencing disability. It has been determined that the human being is constituted as such in interaction with others and requires an acceptance in the community to achieve significant leaming and integration of disabled children at regular physical education pays dividends for them and for their environment.With the completion o f the “First National Study on Disability” is achieved characterize the different areas of participation in society of these people, revealingthe difficulties in school terms, with problems related to low enrollment, dropout, among others.Within the prevailing curriculum framework, the development of pupils at some physical disability means a great effort, both for him and for teachers and the rest of their peers. But an educational community with an open mind and a real acceptance of diversity, can solve many of the difficulties. The difficulties faced by the integrated students relate to accessibility, performance in activities of daily living, autonomy during lessons, requiring mediation in certain leaming.Often integrated students require direct and indirect support performed by professional specialists, enable further the process of integration into theclassroom.Another important factor in the success of the process, is related to the full and active support of families.The greatest difficulties are related to environmental barriere, both attitudinal as procedures or methodologies used, and not related in any way exclusively with difficulties highlighted by the people experiencing disability.The methodological strategies used in regular schools if they are designed and implemented at all times considering the integrated students constitute a facilitator With respect to the elements that facilítate the process, referred to regular classroom teachere were highly committed, in addition to the families involved and sympathetic, rather inviting about the requirements encountered in the classroom, with support specialists, the which may make the guidelines and accompanying due process. Disability can not continué watching something happens to one person, but such influence is the environment in the educational process, that byproviding a favorable environment, it successfully manages to keep the process ofeducational integration.